Analysis Of Teaching Materials For Sixth-Grade Students In Inclusive Classrooms At SDN 2 Bengkala - Hartayanti, Komang Sri Surya; Mastini, Gusti Nyoman (Jayapangus Press, 2024)
Inclusive education seeks to accommodate students with diverse needs, including those with hearing or speech impairments, ensuring equitable learning opportunities. This study examines the media and learning materials used in inclusive classrooms at SDN 2 Bengkala, a public elementary school renowned for its commitment to inclusivity. The research aims to identify effective strategies for integrating digital media and materials that cater to the specific needs of students with disabilities while adhering to the Merdeka curriculum. Using a qualitative approach, data were collected through in-depth interviews with teachers and observations of sixth-grade classroom activities. The findings reveal that inclusive classrooms require digital media featuring visually appealing content, such as animated cartoons, vibrant images, and integrated sign language, accompanied by audio elements. Such materials play a crucial role in maintaining student engagement and ensuring comprehension, particularly for students with hearing or speech impairments. Additionally, alignment with the Merdeka curriculum facilitates a structured yet flexible learning experience, addressing both academic goals and individual needs. The study concludes that visually stimulating and interactive digital media significantly enhance the learning experience in inclusive settings. Incorporating sign language into visual content further bridges communication gaps, fostering a more inclusive learning environment. These findings underscore the necessity of tailoring educational resources to the diverse needs of students in inclusive classrooms, advocating for broader implementation of such practices to promote inclusive education nationwide.